2005
DOI: 10.1016/j.otohns.2004.09.133
|View full text |Cite
|
Sign up to set email alerts
|

A Hystopathological Study of Thyroarytenoid Muscle Invasion in Early (T1) Glottic Carcinoma

Abstract: Our finding TA muscle invasion at the rate of 31.2% in our 16 case series clinically staged as T1 revealed that deep invasion did not always impair the vocal cord mobility. Observing TA muscle invasion at the rate of 50% in cases involving the one-third anterior part of the vocal cord and the anterior commissure suggested that TA muscle invasion in the anterior part did not significantly impair mobility.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
0
1

Year Published

2009
2009
2013
2013

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 7 publications
1
5
0
1
Order By: Relevance
“…A tumor involving AVC may have already invaded the thyroid cartilage and surrounding sub-regions even it represents a small bump on the AVC surface. Therefore, the clinical stage of glottic laryngeal tumors involving AVC might be under-estimated, which may affect the choice of treatment strategy and prognosis [1], [14]. In line with this notion, we found that although all patients were graded as stage T1b stage before the procedure, four patients were actually detected with thyroid cartilage invasion by postoperative pathological evaluation and should be re-graded as T3 stage.…”
Section: Discussionsupporting
confidence: 66%
“…A tumor involving AVC may have already invaded the thyroid cartilage and surrounding sub-regions even it represents a small bump on the AVC surface. Therefore, the clinical stage of glottic laryngeal tumors involving AVC might be under-estimated, which may affect the choice of treatment strategy and prognosis [1], [14]. In line with this notion, we found that although all patients were graded as stage T1b stage before the procedure, four patients were actually detected with thyroid cartilage invasion by postoperative pathological evaluation and should be re-graded as T3 stage.…”
Section: Discussionsupporting
confidence: 66%
“…These depths were well short of achieving muscular layer breach, which rarely occurs at depths shallower than 2.45 ± 0.59 mm (sum of mucosa and submucosa layer depths). Thus, T1-staged tumors are generally limited to the vocal fold and will not impair vocal fold abduction, indicating that T1 tumors are constrained to the submucosa layer [21]. Conversely, some studies have indicated contradictory findings, including a study by Kocatürk and colleagues [21] that showed muscle invasion in 5 of 16 T1 subjects (tumor depth of 2 to 3 mm).…”
Section: Discussionmentioning
confidence: 99%
“…Thus, T1-staged tumors are generally limited to the vocal fold and will not impair vocal fold abduction, indicating that T1 tumors are constrained to the submucosa layer [21]. Conversely, some studies have indicated contradictory findings, including a study by Kocatürk and colleagues [21] that showed muscle invasion in 5 of 16 T1 subjects (tumor depth of 2 to 3 mm). Manola and colleagues [10] also recorded a maximum average tumor depth of 2.18 mm for T1 glottic carcinomas, suggesting that tumors may have breached the muscular layer.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Pored endolarinksa, ovom metodom se pregledaju i baza jezika, valekule i hipofarinks. Smanjena pokretljivost ili nepokretnost glasnica, epiglotisa ili ventrikularnih nabora je posledica submukozne infiltracije tumorom [49]. Pojedine zone larinksa su često teško pristupačne ovom vidu pregleda kao što su: prednja komisura, Morganjijev (Morgagni) ventrikulus, dno piriformnog sinusa i subglotisna regija.…”
Section: Dijagnoza Malignog Tumora Larinksaunclassified